Emergence of High Level Carbapenem and Extensively Drug Resistant Escherichia coli ST746 Producing NDM-5 in Influent of Wastewater Treatment Plant, Seoul, South Korea - Shin, Hanseob; Kim, Yeonghyeon; Han, Dukki; Hur, Hor-Gil (Frontiers in Microbiology, 2021)
High level carbapenem and extensively-drug resistant Escherichia coli strain N7, which produces a variant of New Delhi metallo--lactamase (NDM-5), was isolated from the influent of the Jungnang wastewater treatment plant located on Han river, Seoul, South Korea. Phenotypic and genotypic resistances to carbapenem were tested using agar and broth dilution methods, and a polymerase chain reaction. Whole-genome sequencing was performed to characterize the genetic structure of strain N7. E. coli strain N7, which is an NDM-5 variant, showed high level carbapenem resistance at concentrations of doripenem (512 mg/L) and meropenem (256 mg/L), and extensively-drug resistance (XDR) to fifteen antibiotics. Based on the genomic sequence analysis, two plasmids, a hybrid IncHI2/N-type and an IncX3 type, were present. The former contains a cluster (blaNDM-5-bleMBL-trpF-dsbD) bracketed by multi-insertional sequences, IS3000, ISAba125, IS5 and IS26. The latter carries the following resistance genes: blaCTX-14, aac(3)-IV, aadA1, aadA2, aph(3')-Ia, aph(4)-Ia, sul1, sul2, sul3, dfrA12, fosA3, oqxA, oqxB, mph(A), and floR, and cmlA1. The chromosome, contig3, and contig5 also carry blaCTX-64 and mdf(A), tet(A) and erm(B), tet(M) and aadA22, respectively. Strain N7 also harbours virulence factors (fimH, flu, ecpABCDE, sfmA, hlyE, and gadA). This study demonstrates the emergence of high level carbapenem resistant XDR E. coli strain N7 containing blaNDM-5 in the megacity aquatic environment, Seoul, South Korea. Due to the presence of mobile genetic elements, this strain could horizontally transfer resistance genes, including blaNDM-5 to environmental bacteria. Thus, it is necessary to conduct continuous surveillance for carbapenem resistance in various aquatic environments.